2020
DOI: 10.1016/j.ejor.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Algorithm Design for Hybrid Flowshop Scheduling Problems

Abstract: Industrial production scheduling problems are challenges that researchers have been trying to solve for decades. Many practical scheduling problems such as the hybrid flowshop are N P-hard. As a result, researchers resort to metaheuristics to obtain e ective and e cient solutions. The traditional design process of metaheuristics is mainly manual, often metaphor-based, biased by previous experience and prone to producing overly tailored methods that only work well on the tested problems and objectives. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…According to table 3, ADA has an RDI close to the best results for the small benchmark with all CPU times. We also observed that, on average, the proposed HIGT gave better results for small instances with the three stopping times where the average RDI value is 0.73 for the proposed method while the nearest value is given by ADA of Alfaro-Fernández et al (2020) with an average RDI = 1.32. However, our approach shows a reduction of 44.69% against the closest RDI value.…”
Section: Results Evaluation and Statistical Analysesmentioning
confidence: 67%
See 2 more Smart Citations
“…According to table 3, ADA has an RDI close to the best results for the small benchmark with all CPU times. We also observed that, on average, the proposed HIGT gave better results for small instances with the three stopping times where the average RDI value is 0.73 for the proposed method while the nearest value is given by ADA of Alfaro-Fernández et al (2020) with an average RDI = 1.32. However, our approach shows a reduction of 44.69% against the closest RDI value.…”
Section: Results Evaluation and Statistical Analysesmentioning
confidence: 67%
“…In the literature of HFS, several methods are used with many variants among which we selected 4 from the best methods: the genetic algorithm (GA) of Kahraman et al (2008), the artificial bee colony (ABC) of Pan et al (2012), the improved simulated annealing (HSA) of Naderi et al (2009), the artificial immune system (AIS) of Engin and Döyen (2004). the two methods based on iterated local search ILS V N S and iterated greedy IG V N S of Pan et al (2017a) and finally the auto-designed algorithm (ADA) of Alfaro-Fernández et al (2020). All these seven methods are carefully adapted and re-implemented for the studied problem.…”
Section: Benchmark Competing Methods and Experimental Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of meta-heuristic algorithms should be considered. Statistical calculations showed that the designed automatic algorithm is more efficient than other algorithms in solving the problem [26]. Lee et al, modeled a hybrid flow shop scheduling model using sequence-dependent preparation times.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The hybridization of different kinds of SLS algorithms has shown to be able to generate state‐of‐the‐art algorithms when applied to permutation flowshop (Marmion et al., 2013; Pagnozzi and Stützle, 2019) as well as hybrid flowshop (Alfaro‐Fernández et al., 2020), the unconstrained binary quadratic programming and the traveling salesman problem with time windows (López‐Ibáñez et al., 2017). However, allowing hybridization can generate huge parameter spaces and generate algorithms with a complex, nested structure.…”
Section: Introductionmentioning
confidence: 99%